2018
DOI: 10.2478/ffp-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of financial ratios applicable in the construction of a prediction model for bankruptcy of wood industry enterprises

Abstract: At present, many early warning systems (EWS) are available. Most EWSs have been constructed based on data coming from various branches of economy. As a result, the effectiveness of these models in specific sectors of the national economy is frequently insufficient. There are no models dedicated to a specific branch, particularly the wood industry. Based on the Polish homogenous financial data supplied by the wood industry, it was decided to identify respective indexes, which may be used to construct a sector p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Financial approach is an important method in bankruptcy prediction, since balance sheets and income statements proffer important information for early warning (Adamowicz & Noga, 2018;Cultrera & Brédart, 2016). Financial analysis is the basis for failure and financial distress prediction, as it can reveal the financial stability and strengths as well as weaknesses of firms (Gregova et al, 2020); thereby, financial ratios (representing solvency, activity, profitability, investment, and leverage) are the most frequently used variables in predictions (Fejér-Király, 2015;Šarlija & Jeger, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Financial approach is an important method in bankruptcy prediction, since balance sheets and income statements proffer important information for early warning (Adamowicz & Noga, 2018;Cultrera & Brédart, 2016). Financial analysis is the basis for failure and financial distress prediction, as it can reveal the financial stability and strengths as well as weaknesses of firms (Gregova et al, 2020); thereby, financial ratios (representing solvency, activity, profitability, investment, and leverage) are the most frequently used variables in predictions (Fejér-Király, 2015;Šarlija & Jeger, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The previous analyses investigated five financial indicators, which constituted the independent variables; they were the most suitable for the construction of a bankruptcy prediction model for wood industry enterprises. These indicators were: (i) X1 = PRUSAK2_X3 = current assets/current liabilities, (ii) X2 = HOŁDA_X3 = total income/mean assets, (iii) X3 = ALT-MAN_X4 = equity capital/total debt, (iv) X4 = WIERZBA_ X2 = profit from operating activity -depreciation-to-sales ratio; (v) X5 = PRUSAK1_X2 = operating cost/short-term commitment (Adamowicz and Noga 2018). Based on the tolerance indicator it was concluded that the selected variables (indicators) are not closely correlated and can be used to create a bankruptcy prediction model of wood industry enterprises.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have analyzed the applicability of MBM in predicting the financial situation of wood industry enterprises (Adamowicz and Noga 2017Noga et al 2014). The selection process for appropriate predictors was conducted and described in detail (Adamowicz and Noga 2018). In that process, the authors followed the opinion presented by Jones (2017) indicating that an increase in the number of predictors usually leads to an excessive adjustability, which consequently reduces the general accuracy of the model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations